A neurodinâmica pode explicar a consciência? Uma análise da proposta de Walter Freeman - Oliveira, Rodrigo Travitzki Teixeira de (Universidade Federal de São Carlos, 2006)
This work is a critical analysis of Walter Freeman´s neurodynamic model in several aspects, especially the consciousness as an order parameter that constraints brain dynamics. According to our research, this proposal is not only based in empirical data, but also in ideas as: 1) mathematical metaphor valorization to explain the nature and man; 2) the consciousness as an integrative rational action that limits and selects local fluctuations. We found some gaps in the model, as the author himself admits, and also other interpretations for some empirical results. Therefore, the meaning of neurodynamic patterns found by Freeman remains open. His emergentism is defined by dualism and reductionism denial, and is based in circular causality between whole and parts. Motor cause (and material, we suppose) from the base to the top, and formal and final cause from top to base. It seems to be a pragmatic solution for the mind-brain problem, in order to make possible a wider scientific acceptance of mind effects on the body, contributing to a paradigm change in neuroscience. For Eliasmith, the role of non-linear dynamics would be description, discussion and analysis of complex cognitive systems, as brain. The interpretation of information and dynamic patterns found, however, is not evident nor consensual. This work corroborates such conclusions in particular case of Walter Freeman's model, still highlighting a non scientific role for his work, in the sense of valuing the systemic effects of consciouseness on the body.
Keywords: Filosofia da mente; Neurociência; Cérebro; Auto-organização; Sistemas dinâmicos; Epistemologia; CIENCIAS HUMANAS::FILOSOFIA